2020
DOI: 10.1371/journal.pone.0241953
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of kidney impairment on patients with COVID-19: A meta-analysis of 10180 patients

Abstract: Background The novel coronavirus is pandemic around the world. Several researchers have given the evidence of impacts of COVID-19 on the respiratory, cardiovascular and gastrointestinal system. Studies still have debated on kidney injury of COVID-19 patients. The purpose of the meta-analysis was to evaluate the association of kidney impairment with the development of COVID-19. Methods The PubMed, Embase and MedRxiv databases were searched until May 1, 2020. We extracted data from eligible studies to summariz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
18
0
1
Order By: Relevance
“…These findings were congruent with previous studies. Several studies have suggested that increased BUN can be attributed to acute kidney injury during the course of the disease, which can be a cause of adverse effects [ [53] , [54] , [55] ]. Colombi et al [ 56 ] reported lung involvement area and hypoxia as reliable predictors of ICU admission and mortality among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were congruent with previous studies. Several studies have suggested that increased BUN can be attributed to acute kidney injury during the course of the disease, which can be a cause of adverse effects [ [53] , [54] , [55] ]. Colombi et al [ 56 ] reported lung involvement area and hypoxia as reliable predictors of ICU admission and mortality among COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of authors emphasized the interplay between renal impairment and severe Covid-19 infection, and the effect of the baseline kidney impairment on the prognosis and intensive care unit admission rate of Covid-19 patients. [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…The differences in pathological types suggest that the mechanism of kidney injury is complex. Furthermore, since the prevalence of AKI is significantly higher within COVID-19 patients from intensive care unit (ICU), indicating different mechanisms of AKI between ICU and non-ICU patients [ 11 ].…”
Section: Introductionmentioning
confidence: 99%